RETRACTED: Junior secondary school students' motivation for learning multiple foreign languages in Burundi: a cross-sectional study - Nizigama, Elvis; Fazilatfar, Ali Mohammad; Jabbari, Ali Akbar (Frontiers in Language Sciences, 2023)
This study investigated the motivation of Burundi junior secondary school students learning simultaneously three foreign languages: French, English, and Kiswahili. A 65-item questionnaire was employed to sample the views of 348 (grade 7 through 9) learners from state schools. Using Dörnyei’s (2009) L2 motivational self system as the main theoretical framework, this study specifically explored temporal changes in L2 motivation of the participants over the three-year period across the three target languages. The results indicated that there were significant differences in most of the measured motivational scales across the three languages with ninth grade students scoring significantly lower than their peers from lower school grades. Moreover, the results revealed that L2 learning experience and ideal L2 self were the two variables that respectively predicted most the students’ intended effort to learn each language. One school grade-related difference was that international posture appeared as a significant factor among seventh grade students in relation to French learning and among ninth grade pupils regarding English learning. Another finding, which was unexpected, was that English (L3) appeared to be the most popular foreign language among these students. In the light of the results, pedagogical implications are discussed based on the socio-educational context of Burundi.